2015
DOI: 10.1039/c5ra12158b
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the limited electrochemical activity of NaVP2O7

Abstract: Recently, LiVP 2 O 7 has been investigated as a possible high-voltage substitute for Li 2 FeP 2 O 7 . However, its Na-equivalent, NaVP 2 O 7 , as an economic replacement for Li 2 FeP 2 O 7 has not yet been well understood.Here, for the first time, we report the feasibility of NaVP 2 O 7 as a 3.4 V cathode material for Na-ion batteries. Having a theoretical capacity of 108 mA h g À1 , it shows an initial discharge capacity of 38.4 mA h g À1 at 1/20C (1C ¼ 108 mA g À1 ) in the voltage range of 2.5-4.0 V. Our stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 37 publications
2
28
0
Order By: Relevance
“…NaVP 2 O 7 has a theoretical capacity of 108 mA h g −1 in SIBs. However, the experimental study by Kee et al found that the initial specific capacity was only 38.4 mAh g −1 at 1/20 C (1 C = 108 mA g −1 ) in 2.5–4.0 V. Through DFT calculations and electrochemical characterizations, the authors proposed that the limited electrochemical activity of this compound is not only attributed to sluggish Na + ion migration kinetics, but also intrinsically high resistance, which limits the phase transition kinetics between NaVP 2 O 7 and Na 1− x VP 2 O 7 . Barpanda et al reported a new Na 2 (VO)P 2 O 7 for SIB cathode, and a high redox potential of ≈3.8 V (V 5+ /V 4+ ) with a reversible capacity of ≈80 mAh g −1 was achieved.…”
Section: Vanadium Phosphatesmentioning
confidence: 99%
“…NaVP 2 O 7 has a theoretical capacity of 108 mA h g −1 in SIBs. However, the experimental study by Kee et al found that the initial specific capacity was only 38.4 mAh g −1 at 1/20 C (1 C = 108 mA g −1 ) in 2.5–4.0 V. Through DFT calculations and electrochemical characterizations, the authors proposed that the limited electrochemical activity of this compound is not only attributed to sluggish Na + ion migration kinetics, but also intrinsically high resistance, which limits the phase transition kinetics between NaVP 2 O 7 and Na 1− x VP 2 O 7 . Barpanda et al reported a new Na 2 (VO)P 2 O 7 for SIB cathode, and a high redox potential of ≈3.8 V (V 5+ /V 4+ ) with a reversible capacity of ≈80 mAh g −1 was achieved.…”
Section: Vanadium Phosphatesmentioning
confidence: 99%
“…[205][206][207] Barpanda et al fi rst introduced tetragonal Na 2 (VO)P 2 O 7 , which yields a reversible capacity of 80 mA h g −1 involving the V 4+ /V 5+ redox reaction at 3.8 V vs Na + /Na. [ 205 ] More recently, Kim et al reported a new V-based pyrophosphate compound, Na 4 V 3 (P 2 O 7 ) 4 , as a cathode for NIBs.…”
Section: (14 Of 38)mentioning
confidence: 99%
“…Unfortunately, most of these compounds show significantly inferior electrochemical performance to their Li-equivalents and require further improvement [1,2,3]. While Na is the most abundant alkali metal, Fe and Mn are the most widespread transition metals.…”
Section: Introductionmentioning
confidence: 99%